An introduction to an ancient Chinese algorithm and its modification. Issue 8 (7th November 2016) - He, Chun-Hui
Abstract : Purpose: Every student knows Newton's iteration method from a textbook, which is widely used in numerical simulation, what few may know is that its ancient Chinese partner, Ying Buzu Shu, in about second century BC has much advantages over Newton's method. The purpose of this paper is to introduce the ancient Chinese algorithm and its modifications for numerical simulation. Design/methodology/approach: An example is given to show that the ancient Chinese algorithm is insensitive to initial guess, while a fast convergence rate is predicted. Findings: Two new algorithms, which are suitable for numerical simulation, are introduced by absorbing the advantages of the Newton iteration method and the ancient Chinese algorithm. Research limitations/implications: This paper focuses on a single algebraic equation; however, it is easy to extend the theory to algebraic systems. Practical implications: The Newton iteration method can be updated in numerical simulation. Originality/value: The ancient Chinese algorithm is elucidated to have modern applications in various numerical methods.